The Relationship between Ownership Structure and Corporate Governance of Listed Companies in the Stock Exchange of Thailand - Tayatong, Suwisa; Ratanacharoenchai, Chamaipon; Nomee, Jarassri (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2019)
The purpose of this paper is to investigate the effect of ownership structure on corporate governance in Thailand. Structure of the ownership is measured by the ratio of individual shareholders ownership and other institutions’ ownership such as director ownership, financial institute ownership, foreign ownership and government ownership which took a role in the management and policy for the listed companies. We used data from the year 2016 annual reports of 527 listed companies. Multiple regression analysis was performed to examine factors influencing corporate governance. The results indicate that the dispersed shareholding which was measured by the percentage of Free Float which reflects the individual shareholders ownership has positively and significantly affected corporate governance scoring. This empirical research, nonetheless, confirm that diversified shareholders and institutional investors are the main drive for better corporate governance.